A web-based survey of impact and experience of young people with epilepsy. (4th April 2011) - Rippon, V; Rawnsley, M; Dunkley, C
Abstract : Aims: To understand the opinions of young people with epilepsies regarding the impact of diagnosis and their experience of health services. Methods: Between April and May 2010 an online questionnaire survey was coordinated by Epilepsy Action, a UK epilepsy organisation. Young people with an epilepsy aged 12–20 years were invited to complete the questionnaire via website and social networking sites. Answers to open questions were examined using principal component analysis. Results: 266 young people completed questionnaires (78% female). Median age was 17 (12–20). Regarding education, 86/239 (36%) felt that teachers did not understand what epilepsy is and 173/240 (72%) felt that their school or college work was affected by epilepsy. 154/260 (59%) said they have been given enough information by doctors to understand their epilepsy and 226/261 (87%) understood why it is important to take their medication regularly. 127/262 (48%) of participants agreed that friends would know what to do if they had a seizure. 136/261 (52%) felt that they were sometimes excluded from social activities due to their epilepsy. When asked to describe their epilepsy in one word, commonest themes included 'depressed', 'angry', 'anxious' and 'restricted'. A small number said they felt 'special' or 'unique'. The main impacts of epilepsy reported in free-text areas were negative and concerned driving, socialising, career prospects, medication side-effects and coping educationally. Young people specifically requested more information on the influence of epilepsy on drinking alcohol and contraception. A small number reported positive attitudes and coping strategies. Conclusion: This large consultation of young people demonstrates many perceived restrictions. Quality of life, participation in social activities with peers and educational attainment are important outcome measures. Young people should feel confident about managing their condition in order to achieve independence and to help make a smooth transition to adult health services. This survey highlights concerns which need addressing in the care of those with epilepsy. Consultation of adolescent patients is crucial to help achieve full participation of young people, families and carers in the design and development of epilepsy services.